2
$\begingroup$

So this is the question I have

The Fibonacci sequence is a recurrence system given by $$F_1 = 1, \ F_2 = 1, \ F_{n+2} = F_{n+1} + F_n \qquad (n = 1, 2, 3, \ldots).$$ This question concerns the following conjecture: $$(F_{n+5})^2 - (F_n)^2 = 3((F_{n+3})^2 - (F_{n+2})^2) + 8 F_{n+2} F_{n+3} \qquad (n = 1, 2, 3, \ldots).$$ (a) Confirm that the conjecture is true when $n = 6$.

(b) Prove that the conjecture is true for all integers $n \geq 1$.

But when I go through the solution I don't understand one line (separated and marked).

(b) Let $n$ be any integer such that $n \geq 1$.

$$\begin{align} \left( F_{n+5} \right)^2 - \left( F_n \right)^2 &= \left( F_{n+5} - F_n \right) \left( F_{n+5} + F_n \right) \\ &= \left( F_{n+4} + F_{n+3} - F_{n+2} + F_{n+1} \right) \left( F_{n+4} + F_{n+3} + F_{n+2} - F_{n+1} \right) \\ \\ &= \left( \color{red}{2} F_{n+3} + F_{n+1} \right) \left( 2 F_{n+3} + 2 F_{n+2} - F_{n+1} \right) \tag{*} \\ \\ &= \left( 2 F_{n+3} - F_{n+3} - F_{n+2} \right) \left( 2 F_{n+3} + 2 F_{n+2} - F_{n+3} + F_{n+2} \right) \\ &= \left( 3 F_{n+3} - F_{n+2} \right) \left( F_{n+3} + 3 F_{n+2} \right) \\ &= 3 \left( \left( F_{n+3} \right)^2 - \left( F_{n+2} \right)^2 \right) + 8 F_{n+2} F_{n+3} \end{align}$$ Hence, the conjecture is true for all integers $n \geq 1$

In the marked line, where does the red $\color{red}{2}$ come from?

$\endgroup$
0

2 Answers 2

7
$\begingroup$

He substituted $F_{n+3}+F_{n+2}$ for $F_{n+4}$.

$\endgroup$
1
  • $\begingroup$ OMG so clear! got it! got it! $\endgroup$
    – JackyBoi
    Nov 11, 2012 at 14:35
4
$\begingroup$

Use $F_{n+4}-F_{n+2}=F_{n+3}$ in the first factor and $F_{n+4}=F_{n+3}+F_{n+2}$ in the second factor to obtain the asterisked line from the preceding one.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.